2011
DOI: 10.1111/j.1600-0706.2011.19233.x
|View full text |Cite
|
Sign up to set email alerts
|

Increased bumblebee abundance along the margins of a mass flowering crop: evidence for pollinator spill‐over

Abstract: Although the practice of cultivating mass fl owering crops (MFCs) is seen as a means of counteracting the widespread decline of insect pollinators, no study to-date has evaluated whether the increased pollinator abundance associated with MFCs infl uences pollinator visits to assemblages of adjacent native, non-crop plant species (pollinator ' spill-over ' ). In this study we quantifi ed bumblebee abundance along hedgerow transects in MFC (fi eld bean) vs non-MFC (wheat) margins. Surveys were conducted on east … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
58
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(63 citation statements)
references
References 41 publications
4
58
0
1
Order By: Relevance
“…In addition to Westphal et al (2003), who reported that increased bumblebee densities in MFC resulted in higher visitation rates in P. tanacetifolia, other studies using phytometers b found that MFC facilitated a pollinator spillover. Cussans et al (2010) found that fruit set of Lotus corniculatus increased when planted close to oilseed rape and Hanley et al (2011) observed higher effectiveness of bumblebees visiting flower margins adjacent to MFC during the flowering period. However, the positive effect of MFC on native communities appears to be limited to a restricted number of insect species (Le F eon et al, 2010; Rollin et al, 2013 and to be limited in time (Hanley et al, 2011;Westphal et al, 2009).…”
Section: Facilitation: Spillover Of Shared Pollinatorsmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition to Westphal et al (2003), who reported that increased bumblebee densities in MFC resulted in higher visitation rates in P. tanacetifolia, other studies using phytometers b found that MFC facilitated a pollinator spillover. Cussans et al (2010) found that fruit set of Lotus corniculatus increased when planted close to oilseed rape and Hanley et al (2011) observed higher effectiveness of bumblebees visiting flower margins adjacent to MFC during the flowering period. However, the positive effect of MFC on native communities appears to be limited to a restricted number of insect species (Le F eon et al, 2010; Rollin et al, 2013 and to be limited in time (Hanley et al, 2011;Westphal et al, 2009).…”
Section: Facilitation: Spillover Of Shared Pollinatorsmentioning
confidence: 99%
“…Cussans et al (2010) found that fruit set of Lotus corniculatus increased when planted close to oilseed rape and Hanley et al (2011) observed higher effectiveness of bumblebees visiting flower margins adjacent to MFC during the flowering period. However, the positive effect of MFC on native communities appears to be limited to a restricted number of insect species (Le F eon et al, 2010; Rollin et al, 2013 and to be limited in time (Hanley et al, 2011;Westphal et al, 2009). Contrary to studies on alien plant species, the underlying mechanisms of facilitation are rarely investigated.…”
Section: Facilitation: Spillover Of Shared Pollinatorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Pulses of highly attractive floral resources can create dilution effects, drawing species away from adjacent seminatural habitat and reducing pollination services there (Holzschuh et al, 2011). Yet in spite of the attractiveness of MFC fields, wild bee abundance and richness has been found to be higher in habitats, including hedgerows, in closer proximity to MFC fields (Hanley et al, 2011;Le Féon et al, 2013). The effects of MFCs may be species-specific, with some exhibiting higher preference for MFCs over other resources (Rollin et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Flowering legumes are attractive food sources for pollinators (Hanley et al 2011;Knight et al 2009). Besides, organic farms have more perennial grass fields with low yield and higher diversity of wild plants than conventional farms (Aude et al 2003;Henriksen 2013;Petersen et al 2006).…”
Section: Influence On Nature and Biodiversitymentioning
confidence: 99%